PENGARUH KUALITAS TEKNIS, KUALITAS FUNGSIONAL, PROMOSI PENJUALAN, DAN CITRA PERUSAHAAN TERHADAP KEPUASAN NASABAH (Studi pada PT. BCA Tbk Cabang Tanjungpura Pontianak) - (B31111126), Eko Budi Santoso (Jurnal Manajemen Update, 2018)
ABSTRACT        This study aims to determine and analyze the influence of Quality Engineering, Functional Quality, Sales Promotion and Corporate Image of Customer Satisfaction Bank BCA Tanjungpura Pontianak Branch       The population is the customer of Bank BCA Tanjungpura branch of Pontianak. The sample used is 100 customer respondents from various jobs.       The results of this study indicate that the Quality of Engineering, Sales Promotion and Corporate Image partially affect the Customer Satisfaction of Bank BCA Tanjungpura Pontianak Branch while Functional Quality does not partially affect the Customer Satisfaction of Bank BCA Tanjungpura Pontianak Branch and simultaneously that Quality Engineering, Functional Quality, Promotion Sales and Corporate Image simultaneously to Customer Satisfaction of Bank BCA Tanjungpura Branch Pontianak.  Keywords: Quality Engineering, Functional Quality, Sales Promotion, Corporate Image and Customer SatisfactionDAFTAR PUSTAKAAaker,D.A. 1992.Manajemen Pemasaran Strategis, John Wiley and Sons, New YorkBarney, JB,1991. Firm Resource and Sustained Competitive Advantage, Journal of Management Science, 42 Abdurrahman, A. (2005). Ensiklopedia Ekonomi Keuangan dan Perdagangan. Jakarta: Pradya Paramita.Andi Supangat.2008. Statistik dalam Kajian Deskriptif, Infensi dan Paramatik. Jakarta : Kencana Prenada A, Parasuraman. (2001). The Behaviorial Consequenses of Service Quality, Jurnal of Marketing,Vol 60. Carpenter, J. M., and Fairhurst, A. 2005. Consumer Shopping Value, Satisfaction, And Loyalty For Retail Apparel Brands. Journal of Fashion Marketing and Management, 9(3), 256–269. Cronin J.J And Taylor, S.A.1992. Active Emphatics Listening and Selling Succes.A.Conceotual Framework. Journal of Personal selling and sales Management.Vol.14. pp.55-68 Dick ,A and Basu, K, 1994. Loyalitas pelanggan:Towards An Integrated Conceptual Framework’ Journal of The Academic Marketing science.Vol. 22. No.2. pp 99-113 Diyanthi, Ni Puluh Dharma. 2015. Penagruh Citra Perusahaan, Promosi Penjualan dan Kualitas Pelayanan terhadap Kepuasan Nasabah pada LPD Dsa Pakraman Pajer. Jurnal Manajemen Unyana. Ferdinand, Augusty, 2006. Metode Penelitian Manajemen, Seri Pustaka Kunci    08 / 2006, BP UNDIP Fisher, Joseph, 1998. Contingency Theory Management Control System; Past  ResultAnd Future Direction, Behavioral Research In Accounting Vol. 10, pp.47-64 Ghozali, Imam, 2011. Aplikasi Analisis Multivariate Dengan Program SPSS, Edisi Keempat, Penerbit Universitas Diponegoro. Grover R, Srinivasan V, 1992.Evaluating The Multiple Effects Of Retail Promotions On BrandLoyalty And Brand Switching Segments. J. Mark. Res., 29(1): 76-89. Hair, J. F., Black, W. C., Babin, B. J., Anderson, R. E., and Latham, R. L. (2006). Multivariate Data Analysis (6th ed. Pearson International Edition). Upper Saddle River, NJ: Prentice-Hall. Hsiung, Lin, Chien, 2011. A Study on the Relationships Between the Brand Image and Customer Satisfaction in Catering Businesses, African Journal of Business management Vol. 5 (7732-7739). Mowen, John C ,and Minor, Michael, 1998. Perilaku Konsumen, Erlangga. Onwuchuruba, G. U, 2002. Marketing Financial Services in Nigeria, Lagos:Servo Marketing and Management Services. Margono.(2004). Metodologi Penelitian Pendidikan.Jakarta:RinekaCipta.Jurnal penelitian pendidikan Moch. Nazir. (2003), Metode Penelitian, Salemba Empat, Jakarta, Sugala, Osner. 2016. Analisis Pengaruh Kualitas Teknikal dan Kualitas Fungsional terhadap Kepuasan Pasien (Studi Pada RSUD Kuala Kurun). Jurnal manajemen. Volume III Nomor 2 Sept 2016 Kotler, Philip. 2002. Manajemen Pemasaran, Analisa perencanaan, Implementasi dan control, Edisi Kesembilan, Jilid 1 dan jilid 2, Jakarta, Prehalindo, alih bahasa oleh Hendra Teguh S.E.,A.K., dan Ronny A. Rusli, S.E. Jurnal pemasaran Pi, Wan-and Huang, Hsieh-Hong, 2011. Effects Of Promotion On Relationship Quality And Customer Loyalty In The Airline Industry : The Relationship Marketing Approach, African Journal Of Business Management, Vol. 5 (4403-4414). Porter, M.E. 1980. Teknik Strategi kompetitif untuk menganalisis Industri dan kompetitor.The Free Press, New York. Reynolds, K. E., and Beatty, S. E, 1999. Customer Benefits And Company Of Consequences Customer-Salesperson Relationships In Retailing. Journal of Retailing, 75(1), 11–32. Ryu, Kisang and Heesup Han, 2010. Influence of the Quality of Food, Service, and Physical Environment on Customer Satisfaction and Behavior Intention in Quick-Casual Restaurants : Moderating Role of perceived Price, Journal of Hospitality and Tourism Research. Sugiyono. 2010. Metode Penelitian Pendidikan Pendekatan Kuantitatif, kualitatif, dan R&D.Jurnal statisticSutisna. 2001. Perilaku Konsumen dan Komunikasi Pemasaran. Bandung: PT Remaja Rosdakarya. Yeoh, PL, Jeong, I, 1995. Contingency Relationships Between Entrepreunership,Export Channel Structure and Environment:A Proposed Conceptual Model of Export Performance. European Journal of Marketing. Vol 29 :95 – 115 Zeithaml, Valerie.A. Leonard,L. And Dan Marry, J,. Bitner 2000. Service     Marketing: Integrating Customer Focus Across The Firm, Second Edition, Mc Graw Hill, New York https://aritmaxx.wordpress.com/2010/06/30/variabel-penelitianhttp://dataolah.blogspot.co.id/2012/07/v-behaviorurldefaultvmlo.htmlhttp://duwiconsultant.blogspot.co.id/2011/11/analisis-regresi-linier-berganda.htmlhttp://elib.unikom.ac.id/download.htmlhttp://elib.unikom.ac.id/files/disk1/367/jbptunikompp-gdl-suryanamar-18345-5-daftarp-a.http://girimahendra.blogspot.co.id/2013/05/uji-asumsi-klasik-sebagai-syarat-uji.htmlhttp://jbptunikompp-gdl-rinawatini-16618-4-daftarp-.docxhttps://lib.atmajaya.ac.id/default.aspx?tabID=61&src=a&id=308962http://rumushitung.com/2013/06/08/tabel-r-statistika-dan-cara-membacanya/www.afidburhanuddin.wordpress.com/2013/05/21/penelitian-kuantitatif-dan-kualitatifwww.gurupendidikan.com/5-pengertian-hipotesis-menurut-para-ahli-lengkap/www.seputarpengetahuan.com/2016/04/10-pengertian-hipotesis-menurut-para-ahli-terlengkap.htmlhttp://repository.upi.edu/4010/9/S_PKR_0704687_Bibliographywww.statistikian.com/2013/01/uji-f-dan-uji-t.html